SCREENING OF INTRAUTERINE GROWTH RESTRICTION WITH UTERINE ARTERY DOPPLER BETWEEN 20-24 WEEKS GESTATION IN HIGH-RISK PREGNANT WOMEN IN MNCH FAISALABAD (The Research of Medical Science Review, 2025)
Objectives: To measure frequency of intrauterine growth restriction (IUGR) with uterine artery Doppler between 20–24 weeks gestation in high-risk pregnant women. Study Settings: Department of Gynecology, DHQ/Allied Hospital, Faisalabad. Duration of Study: January 2024 to June, 2024. Data Collection: A descriptive cross-sectional study was conducted on 94 antenatal women with singleton pregnancies between 20–24 weeks gestation, identified as high-risk based on prior obstetric or medical history. All participants underwent uterine artery Doppler ultrasound, assessing pulsatility index (PI), resistance index (RI), and presence of uterine notching. IUGR was diagnosed based on Doppler indices (PI >1.45, RI >0.65, and/or uterine notching) and confirmed by follow-up. Results: The mean age was 27.56 ± 4.59 years. IUGR was diagnosed in 7.4% of cases. Uterine notching was present in 20.2% of participants. Although various clinical and obstetric factors were assessed, no statistically significant associations with IUGR were identified. Conclusion: Uterine artery Doppler between 20–24 weeks gestation serves as a useful screening tool for early detection of IUGR in high-risk pregnancies. Routine second-trimester Doppler screening may improve perinatal outcomes by facilitating timely surveillance and intervention.